Developing the Potential of Using the Mental Health Observation Survey for Referral to Khlong Klang Subdistrict Health Promoting Hospital, Khukhan District, Sisaket Province - อำพันธ์ รุจิรา (Journal of Health Science of Thailand, 2022)
Psychiatric disorders, if treated early at the time of the onset of symptoms and following the advice of a psychiatrist, have a greater chance of recovery. and can live like a normal person, but if the disease is severe Chronic treatment can take a long time and there is a chance that the disease will relapse repeatedly. This study aims to study the potential development of the village health volunteers (VHVs) by comparing scores before and after the training using the mental health observation for referral. Khlong Klang Subdistrict Health Promoting Hospital, Khukhan District, Sisaket Province. Method of study This research was a descriptive research between January 2018 and January 2019. The sample group was volunteers in the area of responsibility Khlong Klang Hospital, Khukhan District, Sisaket Province, 90 people by training to develop the potential of using a mental health observation model Data were collected by a knowledge and attitude questionnaire before and after the training. General information questionnaire 10 items, knowledge assessment form 10 items, attitude assessment form 10 items. The statistics used were pair t-tast, mean and percentage. It was found that after the training, the volunteer had a statistically significant improvement in attitude at the 0.05 level. (P<0.001,95%CI=8.86-10.34) Discuss and summarize recommendations. From the research results, it was found that developing the potential of using the mental health observation form of the Volunteers to refer to Khlong Klang Sub-District Health Promoting Hospital, Khukhan District, Sisaket Province Able to increase knowledge and change the attitudes of the VHV regarding the care of mentally ill patients. Therefore, the results should be extended for further use in other issues.